Preparation method of high magnetic permeability fine crystal CoPt alloy sputtering target

CN122979694APending Publication Date: 2026-10-27ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611288549.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

对于自旋突触器件等对薄膜纯度要求较高的应用场景,杂质会钉扎磁畴,影响器件性能,因此粉末冶金法制备的靶材难以满足要求

Benefits of technology

( 本发明采用真空熔炼—塑性变形—热处理的工艺路线,属于全致密化加工方法,避免了粉末冶金工艺中粉末原料制备、混合、烧结等环节可能引入的氧化物夹杂、吸附气体等杂质。熔炼铸锭经塑性变形和再结晶退火后,组织致密、无残留孔隙,靶材的纯度高、致密度好,能够满足自旋突触器件等高精度应用对薄膜纯度和质量的严格要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979694A_ABST
    Figure CN122979694A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a high-magnetic-permeability fine-crystal CoPt alloy sputtering target material, which comprises the following steps: taking high-purity Co and Pt as raw materials, and preparing Co 20-80 at.% and Pt 20-80 at.%; vacuum induction smelting and ingot casting; solid solution treatment at 1000-1200 DEG C to obtain a uniform A1 phase structure; multi-pass cold rolling, intermediate annealing at 500-800 DEG C when the total deformation amount is 30-60%, and then continuously cold rolling to a total deformation amount of 70-95%; recrystallization annealing and machining to obtain the target material. The application avoids impurity and pore defects through full densification processing, and makes the magnetic permeability of the target material reach more than 40% without adding alloy elements by controlling phase composition and recrystallization texture, and the average grain size is less than 200 mu m, and the phase composition is a single A1 phase. The application can provide high-purity high-magnetic-permeability CoPt target materials for high-end applications such as neuromorphic computing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sputtering target manufacturing, specifically relating to a method for preparing a high magnetic permeability fine-grained CoPt alloy sputtering target for magnetron sputtering, and particularly to a method for preparing a magnetic alloy target suitable for CoPt thin film deposition in the manufacture of neuromorphic computing chips. Background Technology

[0002] CoPt alloys, with their excellent chemical stability, high thermal and electrical conductivity, and unique magnetic properties, are widely used in electronics, electrical engineering, and catalysis. In magnetron sputtering deposition technology, CoPt alloy targets are key raw materials for preparing CoPt-based magnetic thin films, with important applications in magnetic recording media and spintronic devices. In recent years, with the development of spintronic synapses and neuron devices using spin-orbit torque (SOT) flipping technology, CoPt monolayer films have shown promising application prospects in neuromorphic computing, creating new demands for high-quality CoPt alloy sputtering targets.

[0003] Currently, the preparation of CoPt alloy sputtering targets mainly employs powder metallurgy processes. For example, existing methods for preparing CoPt-based sputtering targets primarily utilize powder sintering, with sintering temperatures limited to the range of 400℃ to 1000℃. Specifically, this method first prepares Co-based alloy raw materials into powder via gas atomization, then mixes Pt powder with the Co-based alloy powder in a specific ratio, and finally performs pressure sintering using hot isostatic pressing (HIP). Another existing technology uses a process route of vacuum atomization powder preparation, manual pressure forming, and hot isostatic pressing to prepare CoPt alloy planar sputtering targets. Further technical solutions involve adding boron oxide powder and other oxide powders to the CoPt alloy atomized powder, followed by ball milling, mixing, dispersion, and then pressure sintering.

[0004] However, the above-mentioned powder metallurgy process has the following shortcomings.

[0005] First, the powder metallurgy process easily introduces oxide inclusions and other impurities, affecting the purity of the target material. During preparation, storage, and mixing, powder raw materials inevitably adsorb impurities such as oxygen and moisture. After sintering, these impurities remain inside the target material, reducing its purity. For applications requiring high film purity, such as spin synapse devices, impurities can pin magnetic domains, affecting device performance. Therefore, targets prepared by powder metallurgy are unlikely to meet these requirements. Second, the density of sintered powder targets is limited. Although the density can be increased to over 90% of the theoretical density through methods such as hot isostatic pressing, residual porosity is still unavoidable inside the sintered powder body. These pores can lead to abnormal discharge and particle generation during magnetron sputtering, affecting the quality and stability of the sputtered film. Third, the powder metallurgy process struggles to effectively control the grain orientation and magnetic permeability of the target material. Grain growth and orientation during powder sintering are influenced by various factors, making precise control of grain size distribution and texture difficult. For magnetic targets, magnetic permeability is a key indicator determining whether magnetron sputtering can ignite normally and the stability of the sputtering process. CoPt targets prepared by powder sintering often have low and uneven magnetic permeability.

[0006] Besides powder metallurgy, there have been attempts to prepare CoPt alloy targets using vacuum melting and casting, but the CoPt alloy targets produced by this method also struggle to achieve high magnetic permeability. The main problems with existing melting and casting methods are coarse ingot structure, severe compositional segregation, and the poor plasticity of CoPt alloys at room temperature, making it difficult to refine the structure through conventional plastic processing methods.

[0007] In summary, existing technologies for preparing CoPt alloy sputtering targets suffer from prominent problems such as insufficient purity, limited density, low magnetic permeability, and difficulty in controlling it. There is an urgent need to develop a new method for preparing CoPt alloy sputtering targets with high purity, high density, high magnetic permeability, and uniform microstructure.

[0008] Furthermore, controlling the magnetic permeability of CoPt alloys, as magnetic materials, presents unique challenges. In magnetron sputtering equipment, a permanent magnet or electromagnet is positioned behind the target. The magnetic field needs to penetrate through the target surface to generate magnetic field lines that confine electrons and maintain glow discharge. If the magnetic permeability of the target is too low, the magnetic field lines will be largely diverted by the target, resulting in insufficient residual magnetic field strength on the target surface to initiate glow discharge, thus preventing the sputtering process. Existing methods to improve the magnetic permeability of magnetic targets mainly involve adding non-magnetic alloying elements such as V, Al, Cr, Ti, Mo, and Si to reduce the target's permeability. However, adding alloying elements introduces impurities, altering the target's composition and microstructure, making it unsuitable for applications requiring high purity. Therefore, how to improve the magnetic permeability of CoPt targets through microstructure control without adding alloying elements is a pressing technical challenge in this field. Summary of the Invention

[0009] To address the aforementioned shortcomings in existing CoPt alloy sputtering target preparation technologies, this invention aims to provide a method for preparing high magnetic permeability fine-grained CoPt alloy sputtering targets. This method overcomes the defects of powder metallurgy, which easily introduces impurities and residual porosity. It effectively controls the magnetic permeability of the CoPt alloy target, achieving a magnetic permeability of over 40% through microstructure control without adding alloying elements. This method yields a CoPt alloy sputtering target with fine and uniform grains.

[0010] To achieve the above-mentioned objectives, the present invention adopts the following technical solution.

[0011] This invention provides a method for preparing a high magnetic permeability fine-grained CoPt alloy sputtering target, comprising the following steps: Step 1: Melting and casting ingots. Using Co with a purity ≥99.99% and Pt with a purity ≥99.99% as raw materials, the ingredients are proportioned according to the target composition, with Co content ranging from 20 to 80 at.% and Pt content ranging from 20 to 80 at.%. The proportioned raw materials are placed in a vacuum induction melting furnace, and the melting is carried out under a vacuum degree of not less than 10... -3 The alloy is smelted under the condition of Pa at a temperature of 1600~1800℃. After smelting, the molten alloy is poured into a mold to obtain a CoPt alloy ingot.

[0012] Preferably, the content of Co is 40-60 at.% and the content of Pt is 40-60 at.%. More preferably, the content of Co is 45-55 at.% and the content of Pt is 45-55 at.%.

[0013] Step 2, solution treatment through pre-heat treatment: The CoPt alloy ingot obtained in Step 1 is subjected to solution treatment at a temperature of 1000~1200℃ and a holding time of 2~8 hours, followed by water quenching or rapid cooling to obtain a CoPt alloy billet with a uniform Al phase, i.e., a disordered face-centered cubic structure.

[0014] Solution treatment eliminates compositional segregation in the ingot and yields a well-ductile Al phase microstructure. The Al phase is a disordered face-centered cubic structure with excellent plasticity. CoPt alloys typically exhibit an Al phase structure at room temperature, but compositional segregation and a small amount of ordered phase may exist in the ingot. High-temperature solution treatment can obtain a uniform Al phase microstructure, providing favorable microstructural conditions for subsequent cold plastic deformation.

[0015] Step 3, cold rolling deformation: The CoPt alloy billet obtained in Step 2 is subjected to multiple cold rolling passes at room temperature, with a total deformation of 50-90% and a deformation of 5-15% per pass. The rolling direction can be unidirectional rolling or cross rolling.

[0016] Cold rolling introduces a large number of dislocations and deformation energy through plastic deformation, providing a driving force for subsequent recrystallization annealing. At the same time, the grain breakage and dislocation cell formation during the deformation process create conditions for obtaining fine recrystallized grains. The deformation amount in each pass is controlled at 5-15% to avoid cracking of the sheet due to excessive deformation in a single pass, while ensuring uniform deformation.

[0017] Step 4, intermediate heat treatment: When the total deformation of cold rolling in Step 3 reaches 30-60%, intermediate annealing is performed. The intermediate annealing temperature is 500-800℃, the holding time is 0.5-4 hours, and after annealing, it is cooled to room temperature under a protective atmosphere.

[0018] Intermediate heat treatment eliminates work hardening generated during cold rolling, restoring the material's plastic deformation capacity to facilitate subsequent cold rolling deformation. Simultaneously, intermediate annealing can partially recover deformed microstructures and control the evolution direction of texture. The selection of the annealing temperature is crucial: too low a temperature will not effectively eliminate work hardening; too high a temperature may lead to grain growth or the transformation of the Al phase to the L10 ordered phase. The transformation temperature of CoPt alloys from the disordered Al phase to the ordered L10 phase is approximately 600–825℃; therefore, the intermediate annealing temperature should be controlled within the range of 500–800℃ to avoid excessive precipitation of the L10 ordered phase.

[0019] Step 5, Cold rolling again: After intermediate annealing, continue to cold roll the CoPt alloy billet until the total deformation reaches 70~95%.

[0020] Step 6, recrystallization annealing: The cold-rolled CoPt alloy billet is subjected to recrystallization annealing at a temperature of 500~800℃ and a holding time of 0.5~4 hours. Then it is cooled to room temperature under a protective atmosphere to obtain the CoPt alloy target billet.

[0021] The purpose of recrystallization annealing is to induce recrystallization in the cold-deformed microstructure, resulting in fine equiaxed grains. The selection of the recrystallization annealing temperature requires comprehensive consideration of three aspects: grain refinement, texture control, and magnetic permeability control. If the temperature is too low, recrystallization will be incomplete, leaving residual deformed structures in the microstructure; if the temperature is too high, grain growth will occur, and the transformation of the Al phase to the L10 ordered phase may be induced. The L10 ordered phase has high magnetocrystalline anisotropy and is a hard magnetic phase; its abundant presence will significantly reduce the magnetic permeability of the target material. Therefore, the recrystallization annealing temperature needs to be precisely controlled to achieve complete recrystallization and grain refinement while avoiding the excessive formation of the L10 ordered phase.

[0022] Step 7, Machining: The CoPt alloy target blank obtained in Step 6 is machined by turning, milling, grinding, etc., to produce CoPt alloy sputtering targets of the required size and shape.

[0023] Furthermore, in step three, the total deformation of cold rolling is preferably 60-85%.

[0024] Furthermore, in step three, the deformation amount per pass is preferably 8-12%.

[0025] Furthermore, in step four, the intermediate annealing temperature is preferably 550~750℃, and the holding time is preferably 1~3 hours.

[0026] Furthermore, in step six, the recrystallization annealing temperature is preferably 550~750℃, and the holding time is preferably 1~3 hours.

[0027] Furthermore, in step two, the solution treatment temperature is preferably 1050~1150℃, and the holding time is preferably 3~6 hours.

[0028] Furthermore, in step one, the vacuum induction melting process requires a vacuum level of not less than 10. -2 Pa, with a melting temperature of 1650~1750℃.

[0029] Furthermore, the protective atmosphere in steps four and six is ​​argon or nitrogen.

[0030] The CoPt alloy sputtering target prepared by this invention has an average grain size of less than 200 μm, mainly 20~150 μm, and a maximum grain size of no more than 300 μm; the magnetic permeability of the target is greater than 40%; the phase composition of the target is Al phase, and the volume fraction of Al phase is ≥90%. Preferably, the orientation rate of the (111) plane of the target is greater than 30%, and the orientation rate of the (200) plane is greater than 20%, but less than the orientation rate of the (111) plane.

[0031] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: This invention employs a process route of vacuum melting—plastic deformation—heat treatment, which is a fully densified processing method. This avoids impurities such as oxide inclusions and adsorbed gases that may be introduced during powder metallurgy processes, such as powder raw material preparation, mixing, and sintering. After plastic deformation and recrystallization annealing, the melted ingot has a dense structure with no residual porosity. The target material has high purity and good density, which can meet the stringent requirements for film purity and quality in high-precision applications such as spin synapse devices.

[0032] This invention achieves magnetic permeability regulation by precisely controlling the phase composition and microstructure of the CoPt alloy without adding any alloying elements. A uniform Al phase is obtained through solution treatment, and the formation of a large amount of the L10 ordered phase is avoided by controlling cold deformation and recrystallization annealing processes. Simultaneously, the magnetic permeability of the target material is improved by regulating the recrystallization texture. The CoPt target material prepared by this method can achieve a magnetic permeability of over 40%, significantly superior to CoPt targets prepared by existing powder metallurgy and smelting / casting methods.

[0033] This invention utilizes a series of processes to generate energy through cold deformation, which in turn provides the driving force for recrystallization. Fine equiaxed grains are obtained through recrystallization annealing. By controlling the recrystallization annealing temperature and time, grain growth is suppressed, and the average grain size of the target material is controlled below 200 μm with uniform grain size distribution.

[0034] The CoPt target material prepared by this invention can meet the demand for high-purity CoPt targets in emerging applications such as neuromorphic computing, and has important engineering application value. Attached Figure Description

[0035] Figure 1 This is a grain morphology diagram of the CoPt alloy sputtering target prepared in Example 3 of the present invention.

[0036] Figure 2 This is a statistical diagram of the grain size of the CoPt alloy sputtering target prepared in Example 3 of the present invention.

[0037] Figure 3 The X-ray diffraction pattern of the CoPt alloy sputtering target prepared in Example 1 of this invention. Detailed Implementation

[0038] The present invention will be further described in detail below through specific embodiments and comparative examples. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Example 1

[0039] The specific process for preparing the CoPt alloy sputtering target in this embodiment is as follows: Smelting and casting ingots: Using 99.99% pure Co and 99.99% pure Pt as raw materials, the materials are prepared in a Co 50 Pt 50 ratio (atomic percentage), with a total mass of 10 kg. The prepared raw materials are placed in a magnesium oxide crucible in a medium-frequency vacuum induction melting furnace, and a vacuum is drawn to a vacuum degree of 5 × 10⁻⁶. -3 After Pa, heating and melting began. The melting temperature was 1700℃. After the raw material was completely melted, it was kept under vacuum for 10 minutes, and then cast into a water-cooled copper mold to obtain a CoPt alloy ingot.

[0040] Solution treatment: The CoPt alloy ingot is placed in a protective atmosphere tube furnace and heated to 1100℃ under argon protection. It is held for 4 hours and then quickly removed and water quenched to obtain a CoPt alloy billet with a uniform Al phase structure.

[0041] Cold rolling deformation: The solution-treated billet is subjected to multiple cold rolling passes at room temperature. The deformation amount in each pass is controlled at 8~12%, and rolling is stopped when the total deformation amount reaches 50%.

[0042] Intermediate heat treatment: The cold-rolled billet is heated to 650°C under argon protection, held for 2 hours, and then cooled to room temperature under argon protection.

[0043] Continue cold rolling: After intermediate annealing, continue cold rolling, with the deformation amount controlled at 8~12% per pass until the total deformation amount reaches 85%.

[0044] Recrystallization annealing: The cold-rolled billet is heated to 650°C under argon protection, held for 2 hours, and then cooled to room temperature under argon protection to obtain CoPt alloy target billet.

[0045] Machining: The target blank is machined and turned to the required size and shape to obtain the CoPt alloy sputtering target.

[0046] The microstructure of the target material was observed using a metallographic microscope, and its phase composition and texture were analyzed using X-ray diffraction (XRD). The magnetic permeability of the target material was measured using a Gaussian Hall probe. The results showed that the average grain size of the target material was 85 μm, and the maximum grain size was 180 μm. The target material consisted of a single Al phase. Figure 1 This is the X-ray diffraction pattern of the CoPt alloy sputtering target prepared in this embodiment. From... Figure 1 It can be clearly seen that all the diffraction peaks correspond to the face-centered cubic structure of the A1 phase, i.e., a single A1 phase. The positions of each diffraction peak match well with the standard PDF card. Specifically, the (111) plane orientation rate of the target material is 38%, the (200) plane orientation rate is 25%, and the magnetic permeability of the target material is 52%. Example 2

[0047] The specific process for preparing the CoPt alloy sputtering target in this embodiment is as follows: Melting and casting ingots: Using 99.99% pure Co and 99.99% pure Pt as raw materials, the materials are batched according to a Co 40Pt 60 (atomic percentage) ratio, with a total mass of 10kg. The batched materials are placed in a medium-frequency vacuum induction melting furnace, and the melting is carried out under a vacuum of 5×10⁻⁶. -3 The CoPt alloy ingot was obtained by melting under the conditions of Pa and melting temperature of 1680℃ and casting.

[0048] Solution treatment: The ingot is heated to 1150℃ under argon protection, held for 3 hours, and then water quenched to obtain a CoPt alloy billet with a uniform Al phase structure.

[0049] Cold rolling deformation: The solution-treated billet is subjected to multiple cold rolling passes at room temperature. The deformation amount in each pass is controlled at 8~12%, and rolling is stopped when the total deformation amount reaches 40%.

[0050] Intermediate heat treatment: The cold-rolled billet is heated to 700°C under argon protection, held at that temperature for 1.5 hours, and then cooled to room temperature under argon protection.

[0051] Continue cold rolling: After intermediate annealing, continue cold rolling, with the deformation amount controlled at 8~12% per pass until the total deformation amount reaches 80%.

[0052] Recrystallization annealing: The cold-rolled billet is heated to 700°C under argon protection and held for 1.5 hours. Then it is cooled to room temperature under argon protection to obtain CoPt alloy target billet.

[0053] Machining: The target blank is machined to obtain CoPt alloy sputtering target.

[0054] The test results showed that the average grain size of the target material was 95 μm and the maximum grain size was 200 μm; the target material was a single Al phase; the orientation rate of the (111) plane of the target material was 35% and the orientation rate of the (200) plane was 22%; the magnetic permeability of the target material was 48%. Example 3

[0055] The specific process for preparing the CoPt alloy sputtering target in this embodiment is as follows: Smelting and casting ingots: Using 99.99% pure Co and 99.99% pure Pt as raw materials, the mixture is prepared in a Co 60Pt 40 ratio (atomic percentage), with a total mass of 10kg. The prepared raw materials are placed in a medium-frequency vacuum induction furnace and smelted under a vacuum of 5×10⁻⁶. -3 The CoPt alloy ingot was obtained by melting under the conditions of Pa and melting temperature of 1720℃ and casting.

[0056] Solution treatment: The ingot is heated to 1050℃ under argon protection, held for 5 hours, and then water quenched to obtain a CoPt alloy billet with a uniform Al phase structure.

[0057] Cold rolling deformation: The solution-treated billet is subjected to multiple cold rolling passes at room temperature. The deformation amount in each pass is controlled at 8~12%, and rolling is stopped when the total deformation amount reaches 55%.

[0058] Intermediate heat treatment: The cold-rolled billet is heated to 600°C under argon protection, held for 3 hours, and then cooled to room temperature under argon protection.

[0059] Continue cold rolling: After intermediate annealing, continue cold rolling, with the deformation amount controlled at 8~12% per pass until the total deformation amount reaches 85%.

[0060] Recrystallization annealing: The cold-rolled billet is heated to 600°C under argon protection, held for 3 hours, and then cooled to room temperature under argon protection to obtain CoPt alloy target billet.

[0061] Machining: The target blank is machined to obtain CoPt alloy sputtering target.

[0062] The test results show that: Figure 2 The grain morphology of the CoPt alloy sputtering target prepared in this embodiment is shown below. Figure 2 A uniform recrystallized equiaxed crystal structure can be clearly seen, with clear grain boundaries and no residual pores. Figure 3 The particle size distribution diagram shows that the average grain size of the target is 75 μm and the maximum grain size is 160 μm; the target is a single Al phase; the orientation rate of the (111) plane of the target is 42% and the orientation rate of the (200) plane is 28%; the magnetic permeability of the target is 55%. Example 4

[0063] The specific process for preparing the CoPt alloy sputtering target in this embodiment is as follows: Melting and casting ingots: Using 99.99% pure Co and 99.99% pure Pt as raw materials, the materials are prepared in a Co 50 Pt 50 ratio (atomic percentage), with a total mass of 10 kg. The prepared raw materials are placed in a medium-frequency vacuum induction melting furnace, and the melting is carried out under a vacuum of 5 × 10⁻⁶. -3 The CoPt alloy ingot was obtained by melting under the conditions of Pa and melting temperature of 1700℃ and casting.

[0064] Solution treatment: The ingot is heated to 1100℃ under argon protection, held for 4 hours, and then water quenched to obtain a CoPt alloy billet with a uniform Al phase structure.

[0065] Cold rolling deformation: The solution-treated billet is subjected to multi-pass cold rolling at room temperature, using a cross rolling method (the billet is rotated 90° after each pass). The deformation amount in each pass is controlled at 8~12%, and rolling is stopped when the total deformation amount reaches 50%.

[0066] Intermediate heat treatment: The cold-rolled billet is heated to 650°C under argon protection, held for 2 hours, and then cooled to room temperature under argon protection.

[0067] Continue cold rolling: After intermediate annealing, continue cold rolling using cross rolling method, with the deformation amount controlled at 8~12% per pass until the total deformation amount reaches 85%.

[0068] Recrystallization annealing: The cold-rolled billet is heated to 650°C under argon protection, held for 2 hours, and then cooled to room temperature under argon protection to obtain CoPt alloy target billet.

[0069] Machining: The target blank is machined to obtain CoPt alloy sputtering target.

[0070] The test results showed that the average grain size of the target material was 80 μm and the maximum grain size was 170 μm; the target material was a single Al phase; due to the use of cross rolling, the texture of the target material was more uniform than that of Example 1, with an orientation rate of 32% for the (111) plane and 30% for the (200) plane; the magnetic permeability of the target material was 50%.

[0071] Comparative Example 1

[0072] This comparative example uses existing powder metallurgy methods to prepare CoPt alloy sputtering targets. The specific process is as follows: The raw materials include: Co powder with a purity of 99.9% and an average particle size of 3μm, and Pt powder with a purity of 99.9% and an average particle size of 2μm, mixed in a Co 50 Pt 50 ratio (atomic percentage) for 30 minutes in a ball mill. The mixed powder is then loaded into a hot isostatic pressing (HIP) chamber and evacuated to 10°C. -1 CoPt target material was obtained by hot isostatic pressing at 950℃ and 150MPa for 1 hour with a pressure below Pa.

[0073] The test results showed that: there were a small amount of residual pores in the target material, and the density was about 92% of the theoretical density; the average grain size of the target material was about 15 μm, which was due to the insufficient growth of grains during the powder sintering process, resulting in small grains but pores; a small amount of oxide inclusions were detected in the target material; and the magnetic permeability of the target material was only 25%.

[0074] Comparative Example 2

[0075] In this comparative example, no pre-heat treatment was performed before cold rolling. The specific process is as follows.

[0076] Using 99.99% pure Co and 99.99% pure Pt as raw materials, after melting and casting ingots in a Co 50 Pt 50 ratio (atomic percentage), no solution treatment was performed, and the ingots were directly cold rolled at room temperature. When the total deformation reached 15%, obvious cracks appeared on the edge of the billet. When rolling continued to 20% of the total deformation, the billet fractured, and it was impossible to obtain a complete target billet.

[0077] This comparative example illustrates that if a CoPt alloy ingot is not subjected to solution treatment to obtain a uniform Al phase structure, its room temperature plastic deformation capacity is very poor due to the component segregation and locally ordered phases present in the ingot, and the required deformation amount cannot be obtained by cold rolling.

[0078] Comparative Example 3

[0079] This comparative example used a relatively high recrystallization temperature. The specific process is as follows.

[0080] Using Co with a purity of 99.99% and Pt with a purity of 99.99% as raw materials, and according to the Co50Pt50 (atomic percentage) ratio, the same melting and casting, solution treatment, cold rolling deformation and intermediate heat treatment process as in Example 1 was adopted, but the temperature was increased to 850°C and held for 2 hours in the recrystallization annealing step.

[0081] The test results showed that the average grain size of the target material increased to about 320 μm; XRD analysis showed that obvious diffraction peaks of the L10 ordered phase appeared in the target material, the volume fraction of the A1 phase was about 70%, and the volume fraction of the L10 phase was about 30%; the magnetic permeability of the target material decreased to 18%.

[0082] This comparative example illustrates that excessively high recrystallization annealing temperatures lead to grain coarsening and induce the transformation of the Al phase to the L10 ordered phase. The L10 ordered phase is a hard magnetic phase with high magnetocrystalline anisotropy, which significantly reduces the magnetic permeability of the target material. Therefore, the recrystallization annealing temperature must be precisely controlled within an appropriate range.

[0083] Comparative Example 4

[0084] This comparative example did not employ an intermediate heat treatment process. Details are as follows.

[0085] Using Co with a purity of 99.99% and Pt with a purity of 99.99% as raw materials, and according to the Co50Pt50 ratio (atomic percentage), the same melting and casting process and solution treatment process as in Example 1 were adopted, but no intermediate heat treatment was performed during the cold rolling process, and the material was directly and continuously cold rolled at room temperature until the total deformation reached 85%.

[0086] The results showed that when the total deformation reached approximately 35%, the billet began to exhibit significant work hardening, and the rolling force increased sharply. Continuing rolling to approximately 50% of the total deformation, microcracks appeared at the edges of the billet. When rolling was barely completed to 65% of the total deformation, the billet fractured, making it impossible to obtain a complete target billet. This comparative example illustrates that CoPt alloys exhibit significant work hardening during cold deformation. Without intermediate heat treatment to eliminate work hardening, large-deformation cold rolling cannot be achieved. Therefore, intermediate heat treatment is an indispensable key step in the process route of this invention.

[0087] The above embodiments and comparative examples demonstrate the preparation method of the high magnetic permeability fine-grained CoPt alloy sputtering target provided by the present invention, which can be widely used in the field of magnetron sputtering coating, and is particularly suitable for the preparation of CoPt-based thin films in the fields of neuromorphic computing chips, spintronic devices, and magnetic recording media.

[0088] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention. Parts not described in detail in the present invention are common knowledge to those skilled in the art.

Claims

1. A method for preparing a high magnetic permeability fine-grained CoPt alloy sputtering target, characterized in that, Includes the following steps: Step 1, Smelting and Casting Ingots: Using Co with a purity ≥ 99.99% and Pt with a purity ≥ 99.99% as raw materials, the raw materials are batched according to a Co content of 20~80 at.% and a Pt content of 20~80 at.%. The batched raw materials are placed in a vacuum induction melting furnace, and the melting is carried out under a vacuum degree of not less than 10°C. -3 The melting process is carried out under the condition of Pa, and the melting temperature is 1600~1800℃. After the melting is completed, the CoPt alloy ingot is cast. Step 2, solution treatment: The CoPt alloy ingot obtained in Step 1 is subjected to solution treatment at a temperature of 1000~1200℃ and a holding time of 2~8 hours. Then, it is quenched by water or rapidly cooled to obtain a CoPt alloy billet with a uniform Al phase structure. Step 3, cold rolling deformation: The CoPt alloy billet obtained in step 2 is subjected to multiple cold rolling passes at room temperature, with a deformation amount of 5~15% per pass. Rolling is stopped when the total deformation amount reaches 30~60%. Step 4, intermediate heat treatment: The billet after cold rolling in step 3 is subjected to intermediate annealing at a temperature of 500~800℃ and a holding time of 0.5~4 hours. After annealing, it is cooled to room temperature under a protective atmosphere. Step 5, Cold rolling again: After intermediate annealing, continue cold rolling the CoPt alloy billet until the total deformation reaches 70-95%; Step 6, recrystallization annealing: The cold-rolled CoPt alloy billet is subjected to recrystallization annealing at a temperature of 500~800℃ and a holding time of 0.5~4 hours. Then it is cooled to room temperature under a protective atmosphere to obtain the CoPt alloy target billet. Step 7, Machining: The CoPt alloy target blank obtained in Step 6 is machined to obtain the CoPt alloy sputtering target.

2. The preparation method according to claim 1, characterized in that, In step one, the content of Co is 40~60 at.% and the content of Pt is 40~60 at.%.

3. The preparation method according to claim 1, characterized in that, In step one, the vacuum degree of vacuum induction melting is not less than 10. -2 Pa, with a melting temperature of 1650~1750℃.

4. The preparation method according to claim 1, characterized in that, In step two, the solution treatment temperature is 1050~1150℃, and the holding time is 3~6 hours.

5. The preparation method according to claim 1, characterized in that, In step three, the deformation amount for each pass is 8-12%.

6. The preparation method according to claim 1, characterized in that, In step three, the rolling method is either unidirectional rolling or cross rolling.

7. The preparation method according to claim 1, characterized in that, In step four, the intermediate annealing temperature is 550~750℃, and the holding time is 1~3 hours.

8. The preparation method according to claim 1, characterized in that, In step six, the recrystallization annealing temperature is 550~750℃, and the holding time is 1~3 hours.

9. The preparation method according to claim 1, characterized in that, The protective atmosphere in steps four and six is ​​argon or nitrogen.

10. A CoPt alloy sputtering target prepared by the preparation method according to any one of claims 1 to 9, characterized in that, The target material has an average grain size of less than 200 μm, a magnetic permeability of more than 40%, and a phase composition of A1 phase with a volume fraction of ≥90%. The target material has an orientation rate of (111) plane greater than 30%, an orientation rate of (200) plane greater than 20%, and an orientation rate of (200) plane less than that of (111) plane.